The impact TQM System on Supply Chain Performance through Supply Chain Integration and Employee Satisfaction - Kristianto, Ivan; Tarigan, Zeplin Jiwa Husada (Petra International Journal of Business Studies, 2019)
Indonesia has entered the Southeast Asian free trade market or better known as ASEAN Economic Community (AEC). The economic growth and the increasing number of companies annually will bring some impacts on the competitions for many companies in Indonesia, so they have find their competitive advantage. The biggest competitive advantage of Indonesia is in the primary sector companies which is producing consumer goods from natural raw materials and semi-finished goods. To win the competition, the primary sectors require product standards as the company output by implementing TQM, which usually adopts ISO as the main requirement for exporting their products. This is also the criteria for the research samples. The questionnaires are distributed to 100 companies that have over 100 employees, and the returned questionnaires are 64, with four incomplete questionnaires, making the response rate of 60%. The data analysis is using PLS and proves that all hypotheses are accepted. First, TQM implementation has a positive and significant impact on supply chain integration. Second, TQM implementations in companies are able to create a proper documentation system for each department to facilitate good communication among departments. Third, TQM implementation has a positive impact on supply chain performance and employee satisfaction. Fourth, supply chain integration has a positive impact on employee satisfaction and supply chain performance. Employee satisfaction has a positive effect on supply chain performance. The overall impact of TQM implementation on supply chain performance is 0.4680. TQM implementation brings a positive impact on supply chain integration and supply chain performance, thus increases the total impact of supply chain performance